Breath hydrogen in pneumatosis cystoides intestinalis. Issue 11 (November 1979) - Gillon, J; Tadesse, K; Logan, R F; Holt, S; Sircus, W
Abstract : Pneumatosis cystoides intestinalis (PCI) is an uncommon condition of unknown aetiology. Bacterial gas production may be an important aetiological factor, but experimental evidence in humans has been lacking. We have studied breath hydrogen excretion as an index of bacterial gas production in 12 patients with PCI and have shown that four out of five with demonstrable cysts produced unusually high levels of hydrogen while fasting. This abnormality has not been previously reported. One patient showed resolution of PCI after antibiotic treatment. These findings confirm the importance of bacterial gas production in the pathogenesis of PCI.